Lack of KISS1R expression is associated with rapid progression of conventional renal cell carcinomas - Chen, Ying; Yusenko, Maria; Kovacs, Gyula (The journal of pathology, 2011)
The mortality of patients with conventional renal cell carcinomas (RCC) correlates directly with the development of metastasis, which cannot be reliably predicted simply by TNM classification. The aim of this study was to identify genes associated with the tumour progression. We have analysed the global gene expression in conventional RCCs, including those with and without progression by Affymetrix GeneChip and selected the genes by gene set enrichment analysis. The expression and function of KISS1R was validated by RT-PCR, western blotting and immunohistochemistry and by in vitro experiments. An immunohistochemical and clinical follow-up study showed that lack of KISS1R expression is associated with rapid progression of tumours. In vitro studies showed that activation of KISS1/KISS1R signalling by kisspeptin treatment decreases the motility and invasive capacity of tumour cells. The kisspeptin treatment also induces the expression of KISS1R in tumour cells in vitro and activates signalling in cases without constitutional expression of the receptor. Expression of the KISS1R protein can be used for estimating the prognosis of conventional RCCs. Confirming the activation of KISS1R signalling in vivo may open a way for kisspeptin treatment of patients with conventional RCCs.
First published: 02 December 2010
Gesehen am 28.06.2022